Electrochemically Pretreated Carbon Microfiber Electrodes as Sensitive HPLC-EC Detectors - Zdenka Bartosova; Daniel Riman; Petr Jakubec; Vladimir Halouzka; Jan Hrbac; David Jirovsky (The Scientific World Journal)
The paper focuses on the analysis and detection of electroactive compounds using high-performance liquid chromatography (HPLC) combined with electrochemical detection (EC). The fabrication and utilization of electrochemically treated carbon fiber microelectrodes (CFMs) as highly sensitive amperometric detectors in HPLC are described. The applied pretreatment procedure is beneficial for analytical characteristics of the sensor as demonstrated by analysis of the model set of phenolic acids. The combination of CFM with separation power of HPLC technique allows for improved detection limits due to unique electrochemical properties of carbon fibers. The CFM proved to be a promising tool for amperometric detection in liquid chromatography.